Przemoc prenatalna w obrazie klinicznym pregoreksji - Cichecka-Wilk, Małgorzata (Studia Edukacyjne, 2022)
Prenatal abuse, its causes and consequences, are an important focus of prenatal psychology, a discipline that since the 1920s has occupied scholars studying the earliest stage of human psychological development. The term is used to describe all behavior of the mother towards the child, i.e. her various actions or omissions that negatively affect the child’s health, physical and psychosocial development and life. They can be intentional and deliberate but can also result from unintentional actions. The sources of prenatal abuse are manifold, one of which may be the mother’s illness, for example pregorexia, which is anorexia nervosa in pregnant women. These mothers engage in a range of pathological behaviors that undermine the welfare of their developing children. This is evidenced by the numerous negative consequences, which are manifestations of actions that damage their health and, in some cases, even destroy their lives. Their presence prompts a search for solutions that can prevent or help reduce this phenomenon. There are certain possibilities in the dissemination of correct knowledge about pregorexia and its consequences, adequate social support for pregnant mothers, as well as teaching women parental responsibility and the appropriate attitude towards their prenatal children.